A Tactical Urbanism and Economic Inclusivity: Evaluating the Impact of Spacena Project in a Marginalized Urban Area - Shahed Alhadyan; Mohammad AlRahahleh; Mysaa Khwaileh (Journal of Contemporary Urban Affairs, 2024)
Addressing economic and social inequalities in urban settings, particularly those that affect marginalized groups, is becoming more challenging. In less privileged urban areas, women entrepreneurs face restricted opportunities, specifically in limited retail activities in urban spaces. This study examines the effects of implementing a tactical urbanism solution known as "Retailscape," as represented by Spacena, to address the existing socio-economic disparity. Spacena is an urban furniture piece designed to respect and accommodate PWD, serving as a platform for showcasing locally made products. Employing qualitative methods, including focus groups, interviews, and observations, the research assesses Spacena's economic and social impact. Key themes identified through coding reveal a strong desire for inclusive spaces, economic empowerment, and enhanced social integration. Findings indicate that Spacena is perceived as an opportunity for economic advancement, income generation, and social interaction among residents. However, concerns about project sustainability and regulatory challenges persist. This study demonstrates that tactical urbanism can effectively address economic disparities and foster social cohesion in marginalized communities, suggesting that similar small-scale interventions could have broad, positive implications for sustainable urban design. The findings highlight how Spacena’s low-cost, scalable design and its positive impact on community inclusivity can serve as a model for replicating similar urban interventions in areas with comparable economic and social challenges.